Therapeutic Effect of Ergotope Peptides on Collagen-Induced Arthritis by Downregulation of inflammatory and Th1/Th17 Responses and Induction of Regulatory T Cells - Xiaoyin Niu; Shaohua Deng; Shan Li; Yebin Xi; Chengzhen Li; Li Wang; Dongyi He; Zhaojun Wang; Guangjie Chen (BMC, 2016)
Abstract Rheumatoid arthritis (RA) is a systemic autoimmune disease that results in a chronic and inflammatory disorder. Dynamic balance of helper T cells (Th) 1 and 17 and regulatory T cells (Treg) is broken in RA. Since there is no cure for RA at present, it is necessary to find a truly effective and convenient treatment. Several studies have intended to induce ergotopic regulation to treat autoimmune diseases. This study was undertaken to find potential ergotope peptides and investigate their effects in treating the animal model of RA and their underlying regulatory mechanisms. First, we selected functional ergotope peptides from 25 overlapping peptides derived from the interleukin 2 receptor (IL-2R) α chain, and then used these peptides to treat collagen-induced arthritis (CIA). We showed ergotope peptides as immunomodulatory factors with great benefits at the clinical and pathologic levels. This effect was associated with inhibition of type II collagen (CII)-specific proliferation and autoantibody production as well as induction of antiergotypic immune response, downregulation of both Th1 and Th17 cells and their related components, and emergence of Treg cells that had suppressive action on autoreactive T cells. We also proved that cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) and IL-10 are two important mediators that are critical to Treg suppressive function. Inhibition of Th1 and Th17 in established CIA could be attributed to ergotope-induced Treg cells. Our findings reveal that ergotope peptides induce regulatory immune responses and restore immune tolerance, suggesting that treatment with ergotope peptides may be a novel approach to therapy for RA patients and has good application prospects, with cheap, effective, convenient, wide-spectrum features.